2019
DOI: 10.1186/s40249-019-0555-3
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloidiasis in Ethiopia: systematic review on risk factors, diagnosis, prevalence and clinical outcomes

Abstract: Background: Strongyloidiasis is a gastrointestinal infection caused by the parasitic nematode Strongyloides stercoralis. It is estimated to infect up to 370 million people globally and is predominately found in tropical and subtropical areas of socioeconomic disadvantage. Main body: This systematic literature review identified studies published in the last ten years on the risk factors, diagnosis, prevalence and/or clinical outcomes of strongyloidiasis in Ethiopia. The prevalence of S. stercoralis ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…The prevalence of strongyloidiasis among school children was 6.4% (6.0-6.8%) in this review. A considerable similar report among school-age children is also found in a systematic review conducted in Ethiopia [ 104 ]. This might be justified firstly by the fact that African children are living in unhygienic environment with poor sanitation practices where most children play with contaminated soil and walk barefoot that increases the probability of the entrance of the filariform larvae in the body [ 105 ].…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of strongyloidiasis among school children was 6.4% (6.0-6.8%) in this review. A considerable similar report among school-age children is also found in a systematic review conducted in Ethiopia [ 104 ]. This might be justified firstly by the fact that African children are living in unhygienic environment with poor sanitation practices where most children play with contaminated soil and walk barefoot that increases the probability of the entrance of the filariform larvae in the body [ 105 ].…”
Section: Discussionsupporting
confidence: 74%
“…Even though data on the combination of techniques are not evaluated in this paper, the authors point out the fact that strongyloidiasis is underestimated Ethiopia and that there is a need to approach this issue through the use of a combination of diagnostic methods. [27]. The co-infection of hookworm and S. stercoralis in our sample was as expected: there is evidence in different geographic locations of similar patterns, as both parasites share the same transmission pathway [36,37].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 81%
“…To our knowledge, this is the first study carried out at community level specifically for the detection S. stercoralis in Ethiopia and this is the highest prevalence ever detected at the community level in the country. A very recent review of studies published in the last ten years on strongyloidiasis in Ethiopia [27] showed, a mean prevalence of 2.5% in healthy adults and 11% in HIV positive adults. In Africa, only a study carried out in Gabon showed a prevalence higher than our study, 91.8%, but it was in a population of 15 PSAC [28,29].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…This situation forced the health institutions to employ DSM method for the diagnosis of Strongyloides infection. As a result, under diagnosis and underreporting of the true prevalence of S. stercoralis infection in Ethiopia is a major problem ( Terefe et al, 2019 ). Thus, the aim of this systematic review and meta-analysis was to provide an overview of the prevalence of Strongyloides infection by country and regional label and by diagnostic methods used in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%